2013
DOI: 10.1016/j.molcel.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Autoinhibition and Polo-Dependent Multisite Phosphorylation Restrict Activity of the Histone H3 Kinase Haspin to Mitosis

Abstract: SUMMARY The mitosis-specific phosphorylation of Histone H3 at Thr3 (H3T3ph) plays an important role in chromosome segregation by recruiting Aurora B. H3T3 phosphorylation is catalyzed by Haspin, an atypical protein kinase, whose kinase domain is intrinsically active without phosphorylation at the activation loop. We report here the molecular basis for Haspin inhibition during interphase and its reactivation in M phase. We identify a conserved basic segment that autoinhibits Haspin during interphase. This autoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
92
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 38 publications
9
92
0
2
Order By: Relevance
“…PLK1 is overexpressed in many human tumors and is associated with tumorigenesis (15). It has been recently reported that PLK1 phosphorylates the N terminus of Haspin, leading to its activation and resulting in the phosphorylation of the threonine 3 on histone H3 tail (H3T3) (16,17). Then H3pT3 is recognized by the chromosome passenger complex, resulting in cluster-mediated autophosphorylation and autoactivation of Aurora B (18,19).…”
mentioning
confidence: 99%
“…PLK1 is overexpressed in many human tumors and is associated with tumorigenesis (15). It has been recently reported that PLK1 phosphorylates the N terminus of Haspin, leading to its activation and resulting in the phosphorylation of the threonine 3 on histone H3 tail (H3T3) (16,17). Then H3pT3 is recognized by the chromosome passenger complex, resulting in cluster-mediated autophosphorylation and autoactivation of Aurora B (18,19).…”
mentioning
confidence: 99%
“…This auto-inhibition is released through Cdk1 phosphorylation of Haspin N-terminus followed by the recruitment of Plk1 on the Cdk1 phospho-site and its activation. Activated Plk1 phosphorylates several sites on Haspin N-terminus releasing its activity in a timely manner at the beginning of mitosis triggering H3T3 phosphorylation and CPC recruitment at centromeres [47,48]. Furthermore, Wang et al showed that Aurora B further phosphorylates Haspin Nterminus enhancing its ability to generate H3T3 phospho-sites for Survivin/CPC binding [49] ( Figure 5 lower panel).…”
Section: Regulation Of Haspin Activitymentioning
confidence: 99%
“…However, it is highly phosphorylated during mitosis [13]. Phosphoproteomic studies showed that these phosphorylations are on the N-terminal domain of the protein, where phosphorylation consensus sites for Cdk1, Plk1, and Aurora B are present [45][46][47]. Phosphoryation events on the N-terminal domain at the onset of mitosis trigger conformational changes and influence Haspin kinetics parameters (see above).…”
Section: Regulation Of Haspin Activitymentioning
confidence: 99%
See 2 more Smart Citations